Effect of an infant stimulation program on children - Grace E. Holmes; Richard L. Simpson; Lee Ann Britain (Educational Considerations, 1979)
A planned stimulation program for infants with developmental problems utilizing individual program plans has greater beneficial effects than does traditional periodic follow-up care alone.